The impact on healthcare facilities of the 2024 IV fluids shortage after Hurricane Helene: A mixed methods study - Sophia Gorgens; Ahmad Alshadad; Almas Malek; Amit Boukai; Lindsay Davis; Attila J. Hertelendy; Fadi Issa; Christina Woodward; Amalia Voskanyan; Gregory Ciottone (PLoS ONE, 2026)
Background In September 2024, Hurricane Helene damaged the Baxter International Factory in North Carolina as well as the surrounding infrastructure, causing the factory to shut down production. This resulted in a nationwide shortage of intravenous (IV) fluids. This study sought to characterize the severity of the shortage and define the problems hospitals faced. Methods The National Critical Care Task Force is composed of 200 subject experts in hospital logistics and operations. A mixed methods approach was utilized, gathering quantitative data through an electronic REDCap survey and qualitative data through 1:1 semi-structured interviews. Descriptive summaries, frequencies, and proportions were produced from the quantitative survey data. The interview transcripts underwent thematic analysis using Braun & Clarke methodology. Results Of the 200 critical care task force members, 17 participated in the survey (8.5%). 70.6% worked in urban hospitals and most (88.2%) were affected by the shortage. Hospitals created protocols to minimize IV fluids usage, including cancelling non-urgent surgeries. 11.8% hospitals asked for IV fluids from a neighboring hospital while 17.6% gave IV fluids to a neighboring hospital. 6 task force members participated in semi-structured interview. We identified six major themes: 1) Preparedness, 2) Impact of Shortage, 3) Response and Solutions, 4) Ethics and Resource Allocation, 5) Collaboration, 6) Governance. Conclusion The impact of the IV fluids shortage after Hurricane Helene speaks to the fragility of the current system. This is the first study of its kind to delve into an analysis of the IV fluids shortage and to seek a framework for solutions.